Pengaruh Locus of Control, Kompleksitas Tugas, Due Professional Care, dan Audit Tenure terhadap Audit Judgement pada Kantor Akuntan Publik di Wilayah Kota Medan - Kensa Lie; Ester Halawa; Jenny Zain; Oky Syahputra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The public accounting firm (KAP) obtains permission from the Minister of Finance as an institution for public accountants to provide services. Public Accounting Firms are responsible for auditing the published historical financial statements of all publicly traded companies, most other fairly large companies, and many smaller noncommercial companies and organizations. In reality, there are still publicly traded companies that experience legal problems related to various forms of fraud in accounting practices. The type of research method used in this research is quantitative descriptive methods. The data analysis method used in this research is Partial Least Square (PLS). Based on the results of research conducted on employees at KAP in the Medan city area, it was found that task complexity had an influence on Audit Judgment.